2018
DOI: 10.14744/eej.2018.47965
|View full text |Cite
|
Sign up to set email alerts
|

Crack formation following root-end preparation in roots with the butterfly effect

Abstract: HIGHLIGHTSObjective: To investigate apical cracks in roots that exhibit the butterfly effect and that have undergone apical resection and ultrasonic root-end cavity preparation. The effect of the obturation material was also studied. Methods: Forty extracted single-rooted teeth were decoronated at the cemento-enamel junction. Roots were viewed under a light microscope and coded according to the presence or absence of the butterfly effect. Canals were prepared using ProTaper Next instruments to size X3 and assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In this experimental work, teeth that experienced cracks or fractures after root-end resection were excluded to avoid the illusion of preoperative cracking [22]. SEM analysis confirmed that the ultrasonic technique is always associated with the formation of microcracks, which is in agreement with the results of Peters et al [9][10][11][12][13]. However, our results differ from those of Calzonetti et al [23], in which ultrasonic root-end cavity preparation did not cause root microfractures by using an in situ impression technique, and other studies have also found no microcracks or fractures after root-end cavity preparation with ultrasonic tips [7,27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this experimental work, teeth that experienced cracks or fractures after root-end resection were excluded to avoid the illusion of preoperative cracking [22]. SEM analysis confirmed that the ultrasonic technique is always associated with the formation of microcracks, which is in agreement with the results of Peters et al [9][10][11][12][13]. However, our results differ from those of Calzonetti et al [23], in which ultrasonic root-end cavity preparation did not cause root microfractures by using an in situ impression technique, and other studies have also found no microcracks or fractures after root-end cavity preparation with ultrasonic tips [7,27].…”
Section: Discussionsupporting
confidence: 88%
“…They allow safe access to the long axis of the root canal, decreasing the risk of lateral perforation and preserving an adequate environment for retrograde obturation. However, some studies have reported that apical microcracks appear during root-end preparation with ultrasonic tips [9][10][11][12][13], which increase the risk of apical leakage, reduce the mechanical properties of the root-end, and negatively affect the longterm outcomes of endodontic microsurgery [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sim et al concluded that after RCT, teeth with coronal cracks had a higher survival rate than teeth with radicular cracks ( 18 ). The presence of the butterfly effect was considered as a risk factor for the formation of cracks, following ultrasonic root preparation or root resection, where cracks usually observed in the buccolingual direction ( 19 ).…”
Section: Discussionmentioning
confidence: 99%